Targeting Alpha-Synuclein for the Treatment of Parkinson’s Disease - T. Rohn, Troy (CNS & Neurological Disorders - Drug Targets, 2012)
Parkinson’s disease (PD) is characterized as a neurodegenerative movement disorder presenting with rigidity, resting tremor, disturbances in balance and slowness in movement. An important pathologic feature of PD is the presence of Lewy bodies. The primary structural component of Lewy bodies are fibrils composed primarily of alpha-synuclein, a highly conserved 140 amino acid protein that is predominantly expressed in neurons and which may play a role in synaptic plasticity and neurotransmission. Numerous studies suggest the aggregation and modification of alpha-synuclein as a key step leading to Lewy body formation and neuronal cell loss associated with PD. Because of the central role of alpha-synuclein in PD, it represents a novel drug target for the possible treatment of this disease. In this review, an overview of the role of alpha-synuclein in PD will be discussed with an emphasis on recent studies utilizing an immunization approach against alpha-synuclein as a possible treatment option for this debilitating disease.
Keywords: Immunotherapy